Investigating the Effectiveness of Video Materials in Teaching English for Professional Purposes The case study of: Students of Business English Course at Université de Formation continue - Hammadi Mohamed Idir (My University, 2025)
Abstract This study aims to investigate the effectiveness of integrating video materials in teaching Business English for ESP learners, specifically A2-level students at the University of Continuous Education. The central issue addressed in this research is the limited vocabulary retention and listening comprehension skills observed among students when taught through traditional methods. In response to this pedagogical gap, this study explores video-based instruction as an alternative teaching strategy designed to enhance learners' language competencies through contextualized, authentic exposure to professional communication. To assess the impact of video integration, a mixed-method approach was employed using pre-tests, post-tests, and semi-structured interviews with English teachers. The results provided empirical evidence that video materials significantly improved learners’ comprehension, vocabulary acquisition, and engagement. These findings validate the main hypotheses of the study, confirming the pedagogical value of video content in ESP contexts. Moreover, the research highlights the relevance of multimedia tools in modern Business English classrooms and suggests future studies investigate their impact on other language skills such as speaking and writing performance. ------------- الملخص تهدف هذه الدراسة إلى التحقيق في فعالية دمج المواد المصورة (الفيديوهات) في تدريس اللغة الإنجليزية للأعمال لمتعلمي اللغة لأغراض خاصة (ESP)، وبالتحديد للطلبة من المستوى A2 بجامعة التعليم المستمر، وتتناول هذه الدراسة مشكلة مركزية تتمثل في ضعف احتفاظ الطلبة بالمفردات ومهارات فهم الاستماع عند استخدام الأساليب التقليدية في التدريس، ومن أجل سد هذه الفجوة التربوية، تستكشف الدراسة التدريس المعتمد على الفيديو كاستراتيجية بديلة تهدف إلى تعزيز الكفاءات اللغوية للمتعلمين من خلال التعرض الواقعي والسياقي للتواصل المهني، ولتقييم أثر دمج الفيديو، تم اعتماد منهجية مزدوجة تجمع بين اختبارات قبلية وبعدية ومقابلات شبه مهيكلة مع أساتذة اللغة الإنجليزية. وقد أظهرت النتائج أدلة تجريبية تفيد بأن المواد المصورة حسّنت بشكل ملحوظ فهم المتعلمين، واكتسابهم للمفردات، ومستوى تفاعلهم. وتؤكد هذه النتائج صحة الفرضيات الأساسية للدراسة، مما يبرز القيمة البيداغوجية لمحتوى الفيديو في سياقات ESP، كما تسلط الدراسة الضوء على أهمية الوسائط المتعددة في أقسام اللغة الإنجليزية للأعمال المعاصرة، وتقترح أن تبحث الدراسات المستقبلية في تأثير هذه الأدوات على مهارات لغوية أخرى مثل التحدث والكتابة. ------------- Résumé Cette étude vise à examiner l'efficacité de l'intégration des supports vidéo dans l'enseignement de l'anglais des affaires pour les apprenants en anglais à des fins spécifiques (ESP), notamment les étudiants de niveau A2 à l'Université de l'Éducation Continue. Le problème central abordé dans cette recherche concerne la faible rétention du vocabulaire et les difficultés de compréhension orale observées chez les étudiants lorsque des méthodes traditionnelles sont utilisées. Pour combler cette lacune pédagogique, l’étude explore l’enseignement basé sur la vidéo comme stratégie alternative destinée à renforcer les compétences linguistiques des apprenants à travers une exposition contextualisée et authentique à la communication professionnelle. Afin d’évaluer l’impact de l’intégration des vidéos, une approche méthodologique mixte a été adoptée, reposant sur des pré-tests, des post-tests et des entretiens semi-structurés avec des enseignants d’anglais. Les résultats ont fourni des preuves empiriques montrant que les supports vidéo améliorent de manière significative la compréhension, l’acquisition du vocabulaire et l’engagement des apprenants. Ces résultats valident les hypothèses principales de l’étude, confirmant la valeur pédagogique des contenus vidéo dans les contextes ESP. En outre, la recherche souligne la pertinence des outils multimédias dans les classes modernes d’anglais des affaires et suggère que les futures études examinent leur impact sur d’autres compétences linguistiques telles que l’expression orale et écrite
Keywords: Business English; ESP; Video-Based Instruction; Vocabulary Acquisition; Listening Comprehension; الإنجليزية للأعمال، ESP، التدريس بالفيديو، اكتساب المفردات، فهم الاستماع; Anglais des affaires; enseignement basé sur la vidéo; acquisition du vocabulaire; compréhension orale.